Los dispositivos móviles, en el proceso de aprendizaje de los estudiantes de básica superior de la Unidad Educativa Juan E Verdesoto periodo 2021-2022 - Carriel Chávez, Diana Mercedes (2022)
The present case study is focused on analyzing one of the problems that have become popular lately in the academic area of society, which is about the use of mobile devices in the learning process, this study was carried out in the Juan E. Verdesoto unit taking as a subject of study its students of higher education, to analyze critically, the theories related to the problem of the case, because this population is the one that most uses mobile devices especially when performing their tasks, to obtain information from this population we proceeded to conduct an online survey using the Google form and it was evidenced that most students use mobile devices for academic activities and that they are also predisposed to teachers and the institution allow them to use mobile devices within the classroom because they are a tool that can enhance the skills of students as long as they are used properly, so it is vital that teachers are responsible for guiding students to use them correctly, it is considered pertinent to identify both positive and negative aspects related to the use of mobile devices, and propose strategies that favor a culture of responsibility, respect for the rules and development of new mentalities and practices about the use of new technologies and take advantage of the resources that they offer us today in all social areas.